2022
DOI: 10.1038/s41467-022-34908-z
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of highly crystallized poly(ethylene terephthalate) through cell surface codisplay of bacterial PETase and hydrophobin

Abstract: The process of recycling poly(ethylene terephthalate) (PET) remains a major challenge due to the enzymatic degradation of high-crystallinity PET (hcPET). Recently, a bacterial PET-degrading enzyme, PETase, was found to have the ability to degrade the hcPET, but with low enzymatic activity. Here we present an engineered whole-cell biocatalyst to simulate both the adsorption and degradation steps in the enzymatic degradation process of PETase to achieve the efficient degradation of hcPET. Our data shows that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 90 publications
0
41
0
Order By: Relevance
“…A considerable challenge of PA recycling is that no poylamidase that can degrade highly crystalline PA has been reported until today. However, we anticipate that a solution for crystalline PA recycling by engineering, or discovery of suitable polyamidase, and reaction engineering could soon be achieved, comparably to the great progress achieved for PETases. ,, …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A considerable challenge of PA recycling is that no poylamidase that can degrade highly crystalline PA has been reported until today. However, we anticipate that a solution for crystalline PA recycling by engineering, or discovery of suitable polyamidase, and reaction engineering could soon be achieved, comparably to the great progress achieved for PETases. ,, …”
Section: Resultsmentioning
confidence: 97%
“…However, we anticipate that a solution for crystalline PA recycling by engineering, or discovery of suitable polyamidase, and reaction engineering could soon be achieved, comparably to the great progress achieved for PETases. 9,56,57 NylC was originally identified as endotype 6-AHA oligomer hydrolase. 18 Later, Negoro, Nagai, and colleagues showed that NylC essentially disintegrates thin-layered PA and monitored the hydrolysis of 13−25mers from the solid polymer via gas cluster secondary ion mass spectrometry (SIMS).…”
Section: Mafc Labeling Allows Amine Screening For Directedmentioning
confidence: 99%
“…Other common alternatives are the combination of more enzymes in synergy [ 89 ], the formation of chimaeras with other proteins that have a hydrophobic surface with polymer-binding properties [ 240 ], and the immobilization of enzymes to increase reusability and performance stability over time [ 241 ]. Multiple strategies can be achieved simultaneously [ 242 ]. Such efforts could increase the enzymatic cleavage rate under higher plastic loads, which is one of the best strategies to lower the environmental impact of enzymatic closed-loop PET recycling (see above).…”
Section: Perspectivesmentioning
confidence: 99%
“…15 However, these approaches still need improvements for wide applications due to the lack of degradation capabilities for highly crystalline polyesters. 16 Therefore, there is still great demand for the development of biodegradable polyesters.…”
Section: Introductionmentioning
confidence: 99%
“…Developing biodegradable polymers without sacrificing high-performance material properties is one of the most demanding and difficult issues facing eco-friendly plastics industries. Due to their superior mechanical, thermal, and optical properties, polyesters have been widely utilized for industrial applications. , Terephthalate-based polyesters, such as poly­(ethylene terephthalate) (PET), poly­(butylene terephthalate) (PBT), and poly­(hexylene terephthalate) (PHT), are examples of engineering plastics with high thermal stability, exhibiting degradation temperatures ( T d ) of >400 °C, with variable glass transition temperatures ( T g ) from 10–80 °C that are dependent on alkyl chain lengths in the monomers. However, due to their exceptional stability, they barely decompose in the natural environment and their lifetimes can be extended to 10–100 years. , Recently, enzyme-assisted biodegradations with various types of PET hydrolases, such as esterases, lipases, and cutinases, have been extensively studied. Specifically, enzymatic degradations with leaf-branch compost cutinases were enabled to depolymerize 90% of the PET waste in 10 h at 72 °C . However, these approaches still need improvements for wide applications due to the lack of degradation capabilities for highly crystalline polyesters . Therefore, there is still great demand for the development of biodegradable polyesters.…”
Section: Introductionmentioning
confidence: 99%